Improving Disaster Response in Indonesia Through Culturally Integrated Communication Strategy - Permatasari, Tasya Oktavia; Sinduwiatmo, Kukuh (Journal of Geosciences and Environmental Studies, 2024)
This study aims to analyze the communication strategies employed by the Regional Disaster Management Agency (BPBD) in disaster risk reduction efforts in Sidoarjo. Effective communication is crucial in ensuring community preparedness and resilience against disasters. This research adopts a qualitative method with a case study approach, using in-depth interviews, documentation, and literature review as data collection techniques. The primary data were analyzed using thematic analysis to identify critical patterns and insights. The results reveal that BPBD employs various communication strategies, including social media, public campaigns, and collaboration with local leaders. These efforts are designed to increase public awareness, disseminate early warning information, and foster community participation in disaster preparedness programs. Challenges identified include limited access to remote areas, inadequate resources, and low public engagement due to cultural and socio-economic factors. The discussion emphasizes the importance of integrating local wisdom and community-based approaches to enhance the effectiveness of disaster communication. The study concludes that combining modern technology and traditional communication methods is essential for comprehensive disaster risk reduction. Strengthening stakeholder collaboration and investing in capacity-building initiatives are also recommended for future improvements.